Expansion of shrubs could result in local loss of soil bacterial richness in Western Greenland. Issue 8 (1st July 2020) - Canini, Fabiana; Zucconi, Laura; Coleine, Claudia; D'Alò, Federica; Onofri, Silvano; Geml, József
ABSTRACT: Climate warming in Greenland is facilitating the expansion of shrubs across wide areas of tundra. Given the close association between plants and soil microorganisms and the important role of soil bacteria in ecosystem functioning, it is of utmost importance to characterize microbial communities of arctic soil habitats and assess the influence of plant edaphic factors on their composition. We used 16S rRNA gene amplicons to explore the bacterial assemblages of three different soil habitats representative of a plant coverage gradient: bare ground, biological soil crusts dominated by mosses and lichens and vascular vegetation dominated by shrubs. We investigated how bacterial richness and community composition were affected by the vegetation coverage, and soil pH, moisture and carbon (C), nitrogen (N) and phosphorus (P) contents. Bacterial richness did not correlate with plant coverage complexity, while community structure varied between habitats. Edaphic variables affected both the taxonomic richness and community composition. The high number of Amplicon Sequence Variants (ASVs) indicators of bare ground plots suggests a risk of local bacterial diversity loss due to expansion of vascular vegetation. Abstract : Landscape at Kobbefjord, Nuuk, Greenland.